2009
DOI: 10.1038/cgt.2009.69
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo delivery of novel anticancer fusion protein MULT1E/FasTI via adenoviral vectors

Abstract: We previously demonstrated that a novel fusion protein MULT1E/FasTI expressed by TC-1 tumor cells inhibited tumor growth by simultaneously activating NKG2D expressing cells, such as NK cells, through the MULT1E portion and sending a death signal into cells through the Fas portion (Kotturi et al., Gene Therapy, 2008). In this study, an adenoviral gene delivery system was used to deliver this fusion protein. Our data indicate that adenoviral vector can efficiently deliver the MULT1E/FasTI fusion protein into TC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In our previous studies, we created a fusion gene consisting of the extracellular domain of MULT1 and the transmembrane and introcellular domains of mouse Fas and demonstrated that fusion protein MULT1E/mFasTI activates NK cells and induces apoptosis of tumor cells expressing the protein in vitro and in vivo. 13 The limitation of fusion protein MULT1E/mFasTI is that it can only activate the NK cells that are engaged with the tumor cells expressing the protein and it cannot activate other NK cells in the tumor environment. The bi-functional protein created in this study, however, can provide a local high dose of IL-12, which is able to activate NK cells in the local tumor environment so that the therapy may be more effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we created a fusion gene consisting of the extracellular domain of MULT1 and the transmembrane and introcellular domains of mouse Fas and demonstrated that fusion protein MULT1E/mFasTI activates NK cells and induces apoptosis of tumor cells expressing the protein in vitro and in vivo. 13 The limitation of fusion protein MULT1E/mFasTI is that it can only activate the NK cells that are engaged with the tumor cells expressing the protein and it cannot activate other NK cells in the tumor environment. The bi-functional protein created in this study, however, can provide a local high dose of IL-12, which is able to activate NK cells in the local tumor environment so that the therapy may be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Double enzyme digestion was performed on the purified fragment using BamHI and XhoI. The plasmid pcDNA3.1(+)MULT1E/Neo, created earlier in our lab, 13 was digested with BamHI and XhoI allowing for the insertion of mIL-12 directly downstream of MULT1E in frame. The linearized plasmid was excised and gel purified using a gel purification kit (Qiagen).…”
Section: Construction Of Pcdna31(+)mult1e/mil-12/neo Vectormentioning
confidence: 99%
“…Tumor cells expressing MULT1E-FasTI proliferated significantly more slowly compared to tumor cells without the fusion protein in mouse. Kotturi et al [ 68 ] packaged this fusion gene in an adenoviral delivery vector and directly injected the viral particles into the tumors in mice. This treatment induced the apoptosis of the tumor cells in vivo and significantly delayed the tumor growth.…”
Section: Strategies Of Fusion Proteinsmentioning
confidence: 99%
“…Pulmonary metastasis studies showed that most of the mice completely rejected tumor cells expressing MULT1E/FasTI. [27] We then tried to use an adenoviral gene delivery system to deliver this fusion protein and demonstrated that adenoviral vector can efficiently deliver the MULT1E/FasTI fusion protein into TC-1 cells both in vitro and in vivo as assayed by RT-PCR, FACS analysis, caspase 3 activity and decreased in vivo tumor growth [28].…”
Section: Mult1e/fastimentioning
confidence: 99%